Genetic algorithm based for unit commitment in power systems / Zairul Nizam Sahar - Sahar, Zairul Nizam (2000)
This project report presents a genetic algorithm approach for determining the priority order in the commitment of thermal units in power generation. The purpose of the problem is to properly schedule on/off states at the same times determining the generation of each unit that is to be committed of all power station units in a system to meet the load demand, so that the overall generation cost is a minimum, while satisfying various constraints. This project report examines the feasibility of using genetic algorithm and shows the simulation result to make a comparison of cost generated between the unit thermals.